TRANSFORMASI PADA RUANG PUBLIK KOTA MELALUI KONSEP DESIGN CATALYST - M. Subhi Yuda Wibawa; William Ibrahim (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2011)
Humans as social beings need interaction with the others to show the existence of oneself and the actualization of the surroundings. The need for this is that basically creates social spaces on the order of social life. Social space as a public area for individuals or community groups (communal) to meet each other and socialize. Diversity of community groups who use public space as a social space, making it vulnerable to the interface of public space needs and activities of community groups. The existence of government policy (political), economic activity, social, cultural to participate in shaping the public sphere in the context of transformation. The strength of a design is produced to establish the context of the activities and behavior of various social groups that interact in a public space. Architectural design as a catalyst of change in the function of public spaces to produce a positive reaction from its use for the life of society and social order for the visual character of the surrounding area and as an essential overview of the development area.